Prevalence and Correlates of Binge Drinking among Young Adults Using Alcohol: A Cross-Sectional Survey. (30th June 2014) - Bartoli, Francesco; Carretta, Daniele; Crocamo, Cristina; Schivalocchi, Alessandro; Brambilla, Giulia; Clerici, Massimo; Carrà, Giuseppe
Abstract : Background . Although binge drinking prevalence and correlates among young people have been extensively studied in the USA and Northern Europe, less is known for Southern Europe countries with relatively healthier drinking cultures. Objective . We aimed at analyzing prevalence and correlates of binge drinking in a representative sample of young adults in Italy. Methods . We conducted a cross-sectional survey among alcohol-consuming young adults. We carried out univariate and multivariate analyses to assess associations between recent binge drinking and candidate variables. Results . We selected 654 subjects, with 590 (mean age: 20.65 ± 1.90) meeting inclusion criteria. Prevalence for recent binge drinking was 38.0%, significantly higher for females than males. Multivariate analysis showed that high alcohol expectancies, large amount of money available during the weekend, interest for parties and discos, female gender, cannabis use, influence by peers, and electronic cigarettes smoking all were significantly associated with recent binge drinking, whereas living with parents appeared a significant protective factor. Conclusions . More than a third of young adults using alcohol are binge drinkers, and, in contrast with findings from Anglo-Saxon countries, females show higher risk as compared with males. These data suggest the increasing importance of primary and secondary prevention programmes for binge drinking.